Dilemas del Trabajo y las políticas laborales entre Neoliberalismos y Buen Vivir en América Latina en el Siglo XXI - Vidal Molina, Paula (Ariadna Ediciones, 2021)
In these contradictory times, this collective book is essential because it brings together a series of authors from different countries - Argentina, Brazil, Bolivia, Chile, Ecuador, Spain, Mexico - who analyze and reflect on the socio-economic and political processes developed in Our America in recent decades. The common thread of the analysis perspective is laid in the processes and inspired by the critique of political economy, a fundamental question when it comes to thinking about current society and making a radical critique of capitalist society, taking into account the concrete realities of some of the Latin American countries.